Impact of high-speed rail on high-skilled labor mobility in China. (March 2023) - Feng, Qiyun; Chen, Zhenhua; Cheng, Chuanchao; Chang, Haiqing
Abstract: This paper investigates the impact and mechanism of the opening of High-Speed Rail (HSR) on the mobility of high-skilled labor in China. Using the data of 287 prefecture-level cities in China from 2004 to 2020, this study provides, for the first time, an in-depth assessment of this issue using the PSM-SDID model, combining propensity score matching and spatial difference-in-differences. The least-cost path method is adopted to solve the endogenous problem caused by the non-randomness of HSR. The research results show that HSR has a significant effect on promoting the mobility of high-skilled labor. The effect of HSR on the mobility of high-skilled urban labor is spatially heterogeneous, which is related to the geographical location and scale of the city. From the perspective of urban location, the HSR has a more significant effect on the mobility of high-skilled labor in the cities in the eastern region than that in the central, western and northeast regions. In terms of the urban scale, compared with small and medium-sized cities, HSR is more conducive to the mobility of high-skilled labor in major cities. The results show that HSR can increase the number and scale of enterprises by expanding the scale of the market and attracting the mobility of high-skilled labor. Overall, the research findings provide critical evidence for future infrastructure planning and investment to achieve sustainable and high-quality development. Highlights: Investigated the temporal and spatial differences of the impact of HSR on the mobility of high-skilled labor. HSR promotes the mobility of high-skilled labor by increasing the number and scale of enterprises. HSR has a positive effect on the mobility of high-skilled labor at the national level but has a differential impact at the regional level. Identified the spatial heterogeneous impact of HSR on the mobility of high-skilled labor in different types of cities.